Telocytes: current methods of research, challenges and future perspectives - Bruno D. A. Sanches; Francisco B. S. Teófilo; Mathieu Y. Brunet; Victor M. Villapun; Kenny Man; Lara C. Rocha; Jurandyr Pimentel Neto; Marta R. Matsumoto; Juliana S. Maldarine; Adriano P. Ciena; Sophie C. Cox; Hernandes F. Carvalho (Cell and Tissue Research, 2024)

Bone tissue engineering using 3D silk scaffolds and human dental pulp stromal cells epigenetic reprogrammed with the selective histone deacetylase inhibitor MI192 - Kenny Man; Habib Joukhdar; Xue D. Manz; Mathieu Y. Brunet; Lin-Hua Jiang; Jelena Rnjak-Kovacina; Xuebin B. Yang (Cell and Tissue Research, 2022)
Epigenetics plays a critical role in regulating mesenchymal stem cells’ (MSCs) fate for tissue repair and regeneration. There is increasing evidence that the inhibition of histone deacetylase (HDAC) isoform 3 can enhance MSC osteogenesis. This study investigated the potential of using a selective HDAC2 and 3 inhibitor, MI192, to promote human dental pulp stromal cells (hDPSCs) bone-like tissue formation in vitro and in vivo within porous Bombyx Mori silk scaffolds. Both 2 and 5 wt% silk scaffolds were fabricated and characterised. The 5 wt% scaffolds possess thicker internal lamellae, reduced scaffold swelling and degradation rates, whilst increased compressive modulus in comparison to the 2 wt% silk scaffold. MI192 pre-treatment of hDPSCs on 5 wt% silk scaffold significantly enhanced hDPSCs alkaline phosphatase activity (ALP). The expression of osteoblast-related genes (RUNX2, ALP, Col1a, OCN) was significantly upregulated in the MI192 pre-treated cells. Histological analysis confirmed that the MI192 pre-treated hDPSCs-silk scaffold constructs promoted bone extracellular matrix (ALP, Col1a, OCN) deposition and mineralisation compared to the untreated group. Following 6 weeks of subcutaneous implantation in nude mice, the MI192 pre-treated hDPSCs-silk scaffold constructs enhanced the vascularisation and extracellular matrix mineralisation compared to untreated control. In conclusion, these findings demonstrate the potential of using epigenetic reprogramming and silk scaffolds to promote hDPSCs bone formation efficacy, which provides evidence for clinical translation of this technology for bone augmentation. Graphical abstract